Ratiometric fluorescent sensing carbendazim in fruits and vegetables via its innate fluorescence coupling with UiO-67. (30th May 2021) - Han, Yong; He, Xie; Yang, Weixia; Luo, Xueli; Yu, Ying; Tang, Wenzhi; Yue, Tianli; Li, Zhonghong
Graphical abstract: Highlights: Innate fluorescence of MBC as a response signal of ratiometric fluorescent sensor. Innate fluorescence of MBC endows the sensor with ultra-high selectivity. π-π stacking induced recognition between MBC and UiO-67 with "turn-off" fluorescence. Reverse response of two signals enhances the sensibility with LOD of 3 nmol/L. High anti-interference capability in food samples. Abstract: A ratiometric fluorescent sensor was facilely fabricated using innate fluorescence of carbendazim (MBC) and fluorescent UiO-67 to sensitively and selectively detect MBC in food matrixes. The innate fluorescence of MBC provided a signal at 311 nm (F311 ), and the fluorescent UiO-67 at 408 nm (F408 ) could recognize MBC through π-π stacking inducing fluorescent quenching relied on photoelectron transfer (PET). The ratio (F311 /F408 ) of the fluorescence enhancement of MBC and the quenching of UiO-67 linearly responded to the MBC concentrations of 0–47.6 μmol/L with a low limit of detection (LOD) of 3.0 × 10 −3 μmol/L. The reverse response signals of the sensor enhanced the sensitivity toward MBC and presented remarkable anti-interference capability in complex matrices. The as-prepared sensor was applied to detect MBC residues in apple, cucumber and cabbage, obtaining satisfactory accuracy and precision with the recovery of 90.82–103.45% and RSDs of lower than 3.03%.